Role Of Moringa Oleifera Leaf Extract In Increasing Hemoglobin Levels In Pregnant Rats With Anemia : Role Of Moringa Oleifera Leaf Extract In Increasing Hemoglobin Levels In Pregnant Rats With Anemia - Reny Retnaningsih; Rani Safitri (Universitas Nahdlatul Ulama Surabaya, 2021)
Anemia is one of the epidemic health problems in society and the most common nutritional problem. The Moringa oleifera is rich in excellent dietary content and can complement the body's needs. This study aims to determine Moringa oilefera leaf extract's effectiveness in increasing hemoglobin levels in pregnant rats (Ratus norvegicus) with anemia. This paper used a true experimental research design with a pre-post test randomized control group design. This study utilized female rats (Ratus norvegicus), pregnant 8-12 weeks, weighing 200 grams. Experimental procedures were four treatments with three repetitions. Types of treatment were negative control and positive control (administration of Moringa oilefera leaf extract) at a dose of 0.18 g / head, 0.36 g / head, and 0.72 g/head. Analysis using one way ANOVA with an error rate of 0.05. The results showed p<0.005, which means a significant increase in hemoglobin levels in the group given the treatment of moringa leaf extract at a dose of 0.72 g/head/day. The conclusion and suggestion from this research are public could get information about using natural materials as economically valuable drugs (back to nature)